근거 기반 위암 진료 권고안 - 이준행; Jun Haeng Lee; 김재규; Jae G Kim; 정혜경; Hye Kyung Jung; 김정훈; Jung Hoon Kim; 정우경; Woo Kyoung Jeong; 전태주; Tae Joo Jeon; et al. (The Korean journal of gastroenterology, 2014)
Department of Medicine, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Department of Medicine, Chung-Ang University College of Medicine, Seoul1, Department of Internal Medicine, Ewha Medical Research Institute, Ewha Womans University School of Medicine, Seoul2, Department of Radiology and Institute of Radiation Medicine, Seoul National University College of Medicine, Seoul3, Department of Radiology and Center for Imaging Science, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul4, Department of Nuclear Medicine, Gangnam Severance Hospital, Yonsei University College of Medicine, Seoul5, Department of Pathology, Inha University School of Medicine, Incheon6, Department of Surgery, Ewha Womans University School of Medicine, Seoul7, Center for Gastric Cancer, National Cancer Center, Goyang8, Department of Surgery, Seoul National University Hospital, Seoul9, Department of Surgery, Yonsei University College of Medicine, Seoul10, Department of Internal Medicine, Asan Medical Center, Ulsan University College of Medicine, Seoul11, Department of Internal Medicine, Korea University College of Medicine, Seoul12, Department of Internal Medicine, Hallym University Medical Center, Hallym University College of Medicine, Anyang13, Department of Medical Oncology, Yonsei University College of Medicine, Seoul14, Department of Medicine, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul15, Department of Radiation Oncology, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul16, Department of Pathology, Seoul St. Mary`s Hospital, The Catholic University of Korea, Seoul17, Department of Preventive Medicine, Korea University Medical College, Seoul18, Korea Although, gastric cancer is quite common in Korea, the treatment outcome is relatively favorable compared to that of Western countries. However, there is no Korean multidisciplinary guideline for gastric cancer and thus, a guideline adequate for domestic circumstances is required. Experts from related societies developed 22 recommendation statements for the diagnosis (n=9) and treatment (n=13) based on relevant key questions. Evidence levels based on systematic review of literatures were classified as five levels from A to E, and recommendation grades were classified as either strong or weak. The topics of this guideline cover diagnostic modalities (endoscopy, endoscopic ultrasound, radiologic diagnosis), treatment modalities (surgery, therapeutic endoscopy, chemotherapy, radiotherapy) and pathologic evaluation. External review of the guideline was conducted at the finalization phase. (Korean J Gastroenterol 2014;63:66-81)